Предмет: Алгебра,
автор: hr9999
Розвязати рівняння (х²+3х+1)(х²+3х+3)+1=0
Ответы
Автор ответа:
1
(x²+3x+1)*(x²+3x+3)+1=0
(x²+3x+1)*((x²+3x+1)+2)+1=0
x²+3x+1=t
t*(t+2)+1=0
t²+2t+1=0
(t+1)²=0
t+1=0, t=-1
x²+3x+1=-1
x²+3x+2=0
x₁=-1, x₂=-2
(x²+3x+1)*((x²+3x+1)+2)+1=0
x²+3x+1=t
t*(t+2)+1=0
t²+2t+1=0
(t+1)²=0
t+1=0, t=-1
x²+3x+1=-1
x²+3x+2=0
x₁=-1, x₂=-2
Похожие вопросы
Предмет: Немецкий язык,
автор: кузуешещк
Предмет: Английский язык,
автор: Аноним
Предмет: Другие предметы,
автор: Zhamilya09love
Предмет: Математика,
автор: 666dimdim666
Предмет: Русский язык,
автор: Xomka007